Working Conditions under Lean Production: A Worker-based Benchmarking Study - Lewchuk, Wayne; Robertson, David (Asia Pacific Business Review, 1996)
Benchmarking is being used extensively in management's drive to achieve ‘world class’ levels of performance. The majority of benchmarking studies have little if anything to say about working conditions or the tradeoffs between productivity improvements and the conditions of working life. This article is based on a study which focuses on working conditions as described by workers, raising questions about the tradeoffs betwcen work reorganization and the quality of working life under Lean Production. The results, based on a survey of 1670 workers at 16 different companies, suggest that work life under Lean Production has not improved. Compared with workers in traditional Fordist style plants, those at Lean companies reported their work load was heavier and faster. They rcported work loads were increasing and becoming faster. They reported it was difficult to change things they did not like about their job and that it was becoming more difficult to get time off. While our survey results suggest that working in traditional Fordist plants is far from paradise, they also suggest that working in Lean plants is worse. At a minimum, our results should be viewed as a wake-up call to those who have painted a positive picture of work under Lean Production.